Case Report: Metagenomic Next-Generation Sequencing Confirmed a Case of Central Nervous System Infection With Brucella melitensis in Non-endemic Areas - Cao, Jun; Cai, Qingqing; Su, Wentao; Ge, Zi; Zhao, Hui; Zhou, Xinjian; Ma, Ke; Xia, Zhijie (Frontiers in Medicine, 2021)
Brucellosis is a highly contagious zoonotic disease caused by bacteria which belong to the genus Brucella. It is a major endemic disease in northern China. We reported a rare case of central nervous system (CNS) infection caused by Brucella melitensis in a patient living in non-endemic areas. The patient’s medical history included chronic headache and trunk numbness. Based on the presented clinical symptoms and medical examinations, a clinical diagnosis of binocular uveo-encephalitis was made in local hospital. The patient’s symptoms were unrelieved after treated with empiric therapy. Soon after, the patient was admitted to our hospital due to obnubilation and coma in the trip. We ran a few examinations and sent the cerebrospinal fluid for metagenomic next-generation sequencing (mNGS) immediately. The Magnetic resonance imaging (MRI) examination was unremarkable, and bilateral mastoid inflammation was attached. mNGS suggested a CNS infection caused by Brucella melitensis. Then the results of Serum agglutination test (SAT) and qPCR assay also confirmed that too. After treated with doxycycline, rifampin and cefatriaxone, the patient’s consciousness was restored and headache diminished. Two months later, lumbar puncture was used to check the pressure of cerebrospinal fluid, the total course of treatment was more than 6 months. This case highlighted the potential value of mNGS in early clinal diagnosis. We believe that mNGS may be a complimentary method for rapid identification of CNS infection caused by pathogen.